Effect of plant VOCs and light intensity on growth and reproduction performance of an invasive and a native Phytolacca species in China. Issue 3 (18th March 2022) - Liu, Danfeng; Chen, Li; Chen, Chao; Zhou, Yue; Xiao, Feng; Wang, Yi; Li, Qingjun
Abstract: Invasive plants often pose great threats to the growth of co‐occurring native plant species. Identifying environmental factors that facilitate exotic plant invasion and native species decline are important. In this study, we measured the effects of plant volatile organic compounds (VOCs), light intensity, and their interactions on the growth and reproduction performance of indigenous Phytolacca acinosa, and invasive Phytolacca americana, which has largely replaced the former in China. VOCs of invasive P . americana and low light levels both had negative effects on P . acinosa morphological and reproductive traits (stem length, average leaf number, total number, and length of racemes), and biomass allocation (total biomass, and leaf and flower mass fraction); low light also affected photosynthesis‐related trait (specific leaf area) of P . acinosa . In contrast, VOCs of P . acinosa had no significant effect on P . americana, but low light levels adversely affected its morphological and reproductive traits (stem length, total number, and length of racemes) and biomass allocation (total biomass, stem, and leaf mass fraction). Interactions between plant VOCs and light intensity had no significant effects on P . acinosa or P . americana . Under all experimental treatments, stem length, average leaf area, total number, and length of racemes, Root/Shoot ratio, root and flower mass fraction of P . americana were higher than those of P . acinosa, while average leaf number, specific leaf area, and leaf mass fraction was lower. These results indicated that P . acinosa was sensitive to P . americana VOCs and low light, which might affect the growth of sympatric P . acinosa . P . americana was negatively influenced by low light, but higher plant height and more reproductive organ resource allocation relative to sympatric P . acinosa might contribute to invasion success. Abstract : Phytolacca acinosa was sensitive to Phytolacca americana VOCs and low light, which might affect the growth of sympatric P . acinosa . P . americana was negatively influenced by low light, but higher plant height and more reproductiv organ resource allocation relative to sympatric P . acinosa might contribute to invasion success.